Effects of cognition type on walking gait - Teow, Aaron Boon Hong. (2013)
Walking gait requires the integration of several sources of sensory information and it is an attention-demanding task. The objective of this study is to investigate the relationship between different types of cognitive tasks and walking gait stability. Fifteen young adults comprising eight males and seven females, and fifteen elderly comprising seven males and eight females took part in this study. The young adult participants were required to carry out five different cognitive tasks with three loading conditions while the elderly participants were to carry out the same five cognitive tasks with two loading conditions. The results showed that younger participants have significantly higher gait stability and performed better on the cognitive tasks. However, the relationship between cognitive type and gait stability could not be identified. The results also showed differences in gait stability between genders.